Socio-Economic Differences in the Development of Rural Areas in Federation of Bosnia and Herzegovina – Case Study - Natasa Tandir; Zafer Konakli; Sabahudin Bajramovic (European Scientific Journal, ESJ, 2016)
In Bosnia and Herzegovina some rural municipalities with similar population density are very different regarding key demographic and economic indicators like migration, unemployment and average wages. According to the existing studies in Europe the answer for differential economic performance is firstly in the potential of local community to recognize, strengthen and utilize less mobile assets in the form of economic, social, cultural and natural capital. Secondly, researchers point to the synergy between those assets and external networking and using information and communications technology in reaching new markets and resources. Understanding the reasons for differential economic performance and more or less competitiveness in rural areas of Bosnia and Herzegovina could thus be a key element in devising practical strategies and programs for sustainable rural development. This could also contribute to the programming of Instrument for Pre-Accession Assistance for Rural Development of Bosnia and Herzegovina in the future. The aim of the study is by comparing the most and least developed rural municipalities to investigate the reasons for the differences in economic performance, in particular, to investigate the role of capitals or tangible and less tangible factors influencing development outcomes. In order to achieve that, the authors have chosen high and low performing municipalities according to the criteria of population density, rurality and proximity to large city. In order to have more clear picture, community profiling is conducted and data was collected by surveying community stakeholders. The analysis showed that in high performing municipality all capitals are accessible and properly utilized with space for improvement while low performing municipality has many problems and higher need for change and new strategy of development.